Reliability analysis of a novel IEC 61850-9-2 process-bus based substation automation system architecture. Issue 1 (2nd January 2020) - Gupta, Sunil; Gandhar, Abhishek; Tiwari, Mohit
Abstract: IEC 61850 process-bus based Substation Communication Network (SCN) architecture can facilitate the implementation of 'all-digital' protection and control functions in Substation Automation Systems (SAS). Thus appropriately designed SCN architecture is vital in the reliability, availability and deterministic delay performance of all-digital protection and control functions. This paper has addressed this vital need for any SAS, more specifically for EHV transmission, by proposing a novel IEC 61850-9-2 process-bus based SAS architecture. High reliability of the proposed SAS architecture is demonstrated using Reliability Block Diagram (RBD) approach. The reliability results for the proposed architecture are found to be encouraging and present an option to provide high network availability and protection reliability.